2020
DOI: 10.1142/s2424835520500162
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Wassel Types V and VI Thumb Polydactyly

Abstract: Background: Polydactyly of the thumb is the most common congenital anomaly of the hand, but there have been few reports regarding Wassel types V and VI. The purpose of this study is to present our surgical strategies and outcomes for cases of Wassel types V and VI polydactyly of the thumb. Methods: Twenty-nine thumbs of 29 patients were included in this study; 17 cases were Wassel type V and 12 cases were type VI. Our strategies for initial surgery were appropriate tendon and muscle relocations. Opponensplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Second, our study did not provide information about patientoriented outcomes and functional evaluations. In our experience, it is difficult to measure these parameters using any method in infants or young children and we have focused on obtaining radiographic evaluations for the first web space using a polystyrene cone (Bessho et al, 2020;Takagi et al, 2012Takagi et al, , 2016. Third, we did not have a control group to compare the efficacy of the APB rerouting with other techniques, such extensor tendon reconstruction only.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our study did not provide information about patientoriented outcomes and functional evaluations. In our experience, it is difficult to measure these parameters using any method in infants or young children and we have focused on obtaining radiographic evaluations for the first web space using a polystyrene cone (Bessho et al, 2020;Takagi et al, 2012Takagi et al, , 2016. Third, we did not have a control group to compare the efficacy of the APB rerouting with other techniques, such extensor tendon reconstruction only.…”
Section: Discussionmentioning
confidence: 99%
“…Makino et al (2003) reported long-term follow-up of patients with Type V and Type VI radial polydactyly, where 60% of patients required revision surgery but 80% of these patients who underwent revision surgery did not have any functional improvement. Bessho et al (2020) reported short-term surgical outcomes of 12 patients with Type VI radial polydactyly; three of the five patients with MCP joint radial deviation and one out of seven patients without MCP joint radial deviation required revision surgery, including opponensplasty with stabilization on the ulnar side of the MCP joint or reuse of the transferred abductor pollicis brevis for joint stabilization. In our patients, the abductor pollicis brevis and superficial head of the flexor pollicis brevis were not long enough to reach the MCP joint.…”
Section: Discussionmentioning
confidence: 99%
“…Although adduction deformity of the ulnar duplicate in Type VI radial polydactyly has been described in the literature (Bessho et al., 2020; Ogino et al., 1996), its anatomical basis has not been well discussed. In normal thumb anatomy, muscles associated with first metacarpal abduction include the abductor pollicis longus tendon, abductor pollicis brevis and opponens pollicis (McFarlane, 1962).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thumb duplication is one of the most common congenital hand deformities, characterized by diverse morphological changes [1,2]. The Wassel classi cation is frequently used based on the shape of duplication and X-ray ndings.…”
Section: Introductionmentioning
confidence: 99%